'We might as well be speaking different languages': an innovative interprofessional education tool to teach and assess communication skills critical to patient safety. (25th August 2015) - Gillespie, Colleen; Adams, Jennifer; Hanley, Kathleen; Wagner, Ellen; Shaker-Brown, Amara; Naidu, Mrudula; Kalet, Adina; Zabar, Sondra
Abstract : Introduction: All practicing health professionals must be able to communicate effectively with their colleagues around the care of patients. Better communication between health professionals not only improves patient outcomes, but also cuts down on costly and unnecessary tests or healthcare services. At New York University (NYU), we have addressed the need for interprofessional education (IPE) by incorporating a set of interprofessional objective structured clinical examinations (OSCEs) cases into our performance-based assessment programme to expand the educational tools for interprofessional collaborative (IPC) practice, assessment and feedback. Methods: We identified and operationalised IPC competencies to create an assessment tool for use in IPC clinical cases, delineating core domains and then identifying observable behaviours that represented the broader competencies. IPC cases (for use in OSCEs) were designed in a way that required medical students and residents to collaborate effectively with a health professional from another discipline (standardised registered nurse (RN)) in order to provide quality care to a (standardised) patient. Feedback from the standardised RN and the participants was content analysed and our own experience in implementing was described. Results: This method demonstrates that IPC practice can effectively be incorporated into medical education training and assessment, at the undergraduate and graduate level. We found high internal consistency among items within each of the core IPC competency domains (Cronbach's α 0.80–0.85). Based on both standardised RN and faculty feedback, the cases were effective in discriminating among learners within and across undergraduate medical education (UME) and graduate medical education (GME) levels, and within learners, in identifying individual strengths and weaknesses. Learners found these cases to be realistic, challenging and stimulating. Conclusions: OSCE-based IPC training is a feasible and useful methodology. Ultimately, IPC OSCE cases are training tools that provide learners with a safe environment to practice, receive feedback and develop the critical skills needed for our evolving healthcare system. The next steps are to expand the scope of IPE cases to include more team members, and team work to also incorporate faculty development to ensure that our teachers and role models are effective in providing feedback on IPC practice.